Authoritarian Parenting and Emotional Maturity Among Islamic Junior High Adolescents: Pola Asuh Otoriter dan Kematangan Emosional di Kalangan Remaja SMP Beragama Islam - Nur Machillah; Zaki Nur Fahmawati (Psikologia : Jurnal Psikologi, 2026)
General Background: Emotional maturity is an essential aspect of adolescent psychological development because it shapes self-control, social adjustment, and emotional regulation during early adolescence. Specific Background: Parenting style, particularly authoritarian parenting, is considered one of the important family-related factors associated with adolescent emotional development in Islamic junior high school settings. Knowledge Gap: Previous studies have reported inconsistent findings regarding the relationship between authoritarian parenting and emotional maturity among adolescents, while evidence from Madrasah Tsanawiyah students in Sidoarjo remains limited. Aims: This study aimed to examine the relationship between authoritarian parenting style and emotional maturity among adolescents aged 12–15 years at MTS X Sidoarjo and to identify factors related to emotional maturity development. Results: The study applied a quantitative correlational design involving 100 students selected through saturated sampling. Data were collected using emotional maturity and authoritarian parenting scales. Statistical analysis showed a significant relationship between authoritarian parenting and adolescent emotional maturity with a Pearson correlation coefficient of 0.526 and significance value of 0.000 (p < 0.05). The emotional maturity scale demonstrated Cronbach’s Alpha reliability of 0.745, while the authoritarian parenting scale obtained 0.692. Novelty: This study provides empirical evidence regarding the association between authoritarian parenting and emotional maturity among adolescents in an Islamic junior high school context. Implications: The findings contribute to the understanding of adolescent emotional development and may support parents, teachers, and school counselors in recognizing the role of parenting patterns in adolescent emotional regulation and psychosocial adjustment.Highlights: Significant correlation identified between parental control patterns and adolescent emotional development. Statistical testing confirmed normal data distribution and meaningful Pearson correlation outcomes. Family caregiving patterns were associated with psychosocial regulation among students aged 12–15 years. Keywords: Authoritarian Parenting; Emotional Maturity; Adolescents; Parenting Style; Islamic Junior High School